Peranan Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di SMP N 1 Kecamatan Wayaloar Kabupaten Halmahera Selatan - Odu, Devyand; Mandey, Jantje; Rares, Joyce Jacinta (Sam Ratulangi University, 2015)
Abstract: The purpose of this study was to determine the role of the Leadership Principal inImproving Teacher Performance in the Junior High School 1 Subdistrict Wayaloar as the Decree ofthe Minister of National Education (Education) No. 162 of 2003 on Guidelines for the Assignment ofTeachers as the Principal stated that the task of the principal as an Educator, Supervisor , leadersand providers of motivation. To determine the role of school leadership in improving teacherperformance, the research method used is qualitative method where the researcher as the keyinstrument consists of 7 (seven) research informants.The role of school leadership in improving teacher performance in the Junior High School 1Wayaloar the District has not been effective in this regard are as Supervisor, Leader, Educator, andgiving motivation. Because based on the results of field research shows that principals as educators,supervisor, leader and motivator has not done how expectations of students and parents. as well asthe lack of control and supervision functions of principals on teacher performance, so most apatheticteachers with duties as teachers. As well as employee productivity or decreases in carrying out theduties of teachers and ultimately have implications on student interest less serious.To improve the performance of teachers is needed role of school leadership in the execution of dutyas the leader and protector as the Decree of the Minister of National Education (Education) No. 162of 2003 on Guidelines for the Assignment of Teachers as the Principal stated that the task of theprincipal as Educator Supervisor, Leader and giving motivation to the performance of the employees.The role of principals in improving teacher performance is expected to provide advice to the teachersin implementing the task even carry out the evaluation or analysis of teacher performance results,oversees all the activities of teachers either control directly or indirectly, and the moving of staff andemployees in carrying out the task. As well as the expected presence of motivation or encouragementfrom the principal to the implementation of the tasks the teachers in the form of an appreciation ofthe performance to be achieved in order to increase labor productivity of employees / teachers.Keywords: Role of Leadership Principal, Teacher Performance